Synthesis and growth mechanistic studies of materials diffusion enabled colloidal nanocrystals for emerging applications - Mao, Rundong (Curtin University, 2024)
We summarized the morphology and applications of nanoparticles formed by Ostwald ripening and Kirkendall effect; studied the interesting phenomenon of Ostwald ripening in the synthesis of Zinc Chalcogenide Quantum Rods; obtained a unique structure when synthesizing copper phosphide nanocrystals and further analysed this growth mechanism affected by the Kirkendall effect; based on the obtained various structures and compositions of Cu3P nanocrystals, we studied their The Carbon Dioxide Reduction Reaction (CO2RR) performance.